Transitivities of student conscience in law school: Paulo Freire Group’s critical experience in UFPR - Pereira, Natalia Demes Bezerra Tavares (2022)
The purpose of this essay is to present the experience of Paulo Freire Group, created in the “Universidade Federal do Parana” Law School, during the 2000s. Based on primary sources – such as e-mail messages, debates reports, systematized documents of student interventions and published texts – this paper intends to recompose some of the main moments of the group, relating it to its context, its composition and its intentions towards a practical performance. This article intends not only to report but also to evaluate the contributions that came with the experience of thinking about legal education through Freire´s categories. From notions like transitive conscience, criticality, dialogicity and praxis, it´s possible to notice movements of a university student collective in law school towards problematizing education, as much as Paulo Freire’s work´s potencial for the legal area.